2018
DOI: 10.1093/heapol/czy041
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and clinical effectiveness of a community-based non-communicable disease treatment programme in rural Mexico: a difference-in-differences analysis

Abstract: Non-communicable diseases (NCDs) account for the five largest contributors to burden of disease in Mexico, with diabetes representing the greatest contributor. However, evidence supporting chronic disease programmes in Mexico is limited, especially in rural communities. Compañeros En Salud (CES) partnered with the Secretariat of Health of Chiapas, Mexico to implement a novel community-based NCD treatment programme. We describe the implementation of this programme and conducted a population-based, retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Working with the local health authorities in rural communities in the Sierra Madre mountains, CES revitalized nearly a dozen rural clinics and connected them to 4 cadres of CHWs (locally known as Acompañantes) that were initially focused on providing treatment support for: (1) NCDs, (2) maternal and newborn health, (3) mental health, and (4) child development and nutrition (including early childhood stimulation). Although a stepped-wedge analysis showed that the NCD-focused CHW program had helped achieve some of the best rates of clinical control for NCDs in the region, 11 , 12 the team saw the potential for the NCD and maternal/newborn health cadres to be collapsed into a single cadre through the HHM. In 2019, after regular consultation with the teams in Malawi and Liberia, the Mexico team piloted a new CHW program that moved away from a physician-directed vertical care model, toward a model where CHWs could have more autonomy to use algorithms for screening, follow-up, and referral to the health center.…”
Section: Country Specificsmentioning
confidence: 99%
“…Working with the local health authorities in rural communities in the Sierra Madre mountains, CES revitalized nearly a dozen rural clinics and connected them to 4 cadres of CHWs (locally known as Acompañantes) that were initially focused on providing treatment support for: (1) NCDs, (2) maternal and newborn health, (3) mental health, and (4) child development and nutrition (including early childhood stimulation). Although a stepped-wedge analysis showed that the NCD-focused CHW program had helped achieve some of the best rates of clinical control for NCDs in the region, 11 , 12 the team saw the potential for the NCD and maternal/newborn health cadres to be collapsed into a single cadre through the HHM. In 2019, after regular consultation with the teams in Malawi and Liberia, the Mexico team piloted a new CHW program that moved away from a physician-directed vertical care model, toward a model where CHWs could have more autonomy to use algorithms for screening, follow-up, and referral to the health center.…”
Section: Country Specificsmentioning
confidence: 99%
“…A complex primary care intervention in Mexico involving a new cadre of community health workers, supply chain improvements, active casefinding, and education support for rural doctors did not lead to any significant improvement in blood pressure control among the population of Chiapas State. 43 Medication-specific issues: In addition to problems associated with purchasing medication (see above), 4 studies reported on availability (or lack thereof) of medicine. 30,34,42,45 Unsurprisingly, all reported lack of access, at health facilities, 42 in pharmacies, 34 and more generally 45 as a barrier to adherence.…”
Section: Demographics and Socio-economic Factorsmentioning
confidence: 99%
“…Mexico achieves a lot to decrease morbidity and mortality associated with undernourishment, transmittable infectious diseases such as diarrheal diseases and sanitation, especially among the pediatric population [53][54][55] . Nevertheless, the fifth principal burden of chronic NCDs became the major basis of public health apprehension [54][55][56] . Additionally, diabetes mellitus appears as the sole principal cause of disability-adjusted life years and expected to deteriorate in the upcoming day 57,58 .…”
Section: Amexicomentioning
confidence: 99%